Analisis Pemanfaatan Sampah Plastik Berjenis PET Pada Paving Block: Analysis Of the Use of PET Type Plastic Waste in Paving Blocks - Zafran, M. Rafi; Nurhendi, Revianty Nurmeyliandari; Chandra, Denie (Universitas Negeri Surabaya, 2024)
Plastic waste, especially Polyethylene Terephthalate (PET), is becoming a environmental problem due to the increasing use of plastic in daily life. Solution to reduce the negative impact of plastic waste is utilize in the construction industry, such as in the manufacture of paving blocks. Research intends to evaluate the utilization of PET plastic waste in manufacture of concrete bricks, with a focus on testing compressive strength and water absorption capacity. The method used follows the standard of SNI 03-0691-1996, with three variations of the mixture between sand and PET plastic: 30% sand: 70% plastic, 40% sand: 60% plastic, and 50% sand: 50% plastic. Paving blocks made based on the predetermined mix ratio, and tested for compressive strength and water absorption. Data obtained were analyzed to determine the effectiveness of using PET plastic as a substitute material in paving blocks. Results showed that a mixture with a ratio of 50% sand: 50% plastic produced the highest compressive strength value of 12.41MPa. Water absorption also evaluated, showing adequate performance for paving block applications. Results of this research are useful for the construction industry as alternative material that is more environmentally friendly, to contributing manage plastic waste in a sustainable manner.